Analisis Pengaruh Tax Avoidance, Leverage (DER) dan Firm Size Terhadap Firm Value (Studi Pada Perusahaan Real Estate dan Properti yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Kurnia Kurnia; Dudi Pratomo; Ahmad Fachrizal (Accounthink, 2018)
One of the most highlighted by investors in assessing the performance of Real Estate and Property firms is Firm Value which the ratio used in this research is Tobins'Q. Tobins'Q is used to measure management's ability to manage and take action to maximize overall returns from total assets owned. This research aimed to analyze the effect  of Tax Avoidance, Leverage (DER), and Firm Size on Firm Value, Study on Real Estate and Property Companies Listed In Indonesia Stock Exchange Year 2013-2015. The data used in this research is obtained from financial statement data. Sample selection technique used is purposive sampling and obtained 28 companies with research period in 2013-2015. Data analysis method in this research is panel data regression analysis using software Eviews version 9. The results showed that simultaneously Tax Avoidance, Leverage (DER), and Firm Size have significant effect to Firm Value. While partially Tax Avoidance has a significant negative effect on Firm Value, Leverage (DER) does not affect Firm Value, while Firm Size has a significant positive effect to Firm Value. This indicates that investors and company should be aware on tax avoidance practice and firm size to increasing firm value.